INOVASI PENGOLAHAN JAHE MENJADI SERBUK JAHE INSTAN UNTUK MINUMAN HERBAL BAGI MASYARAKAT DI KECAMATAN LAIS KABUPATEN BENGKULU UTARA - Ajuanda Puteri; Ferry Lismanto Syaiful (LPPM Universitas Andalas, 2023)
Instant ginger powder is one of the famous ginger processed innovations that can be used as a primary ingredient in delicious and beneficial health drinks. Using instant ginger powder in health drinks is an effective and delicious way to gain health benefits. The objectives of this activity are: 1. to provide education on the use of ginger and innovations in its processing, 2. to increase public knowledge and understanding in using ginger as a health drink. This activity was carried out in Pal 30 Village, Lais District, North Bengkulu. The methods used in this activity are counseling, demonstration of processing ginger into ginger powder, and evaluation. The activity results were that participants gained knowledge regarding various aspects of ginger, such as types of ginger, health benefits of ginger, and methods of processing ginger into ginger powder. Participants also understand the correct drying, storage, and packaging processes. In training activities, participants gain practical skills in processing ginger into ginger powder, including selecting quality ginger, peeling, slicing, drying, storing, and packaging correctly. These skills are essential in improving good product quality. From this activity, this training significantly impacts increasing participants' knowledge and skills, as well as the potential for business development. Furthermore, it can be the first step in exploiting the valuable potential of ginger in business development and increasing people's income. This training can encourage innovation in ginger products. It is hoped that after carrying out this activity, the community can open a business from this ginger product, considering the large market interest in this health drink product so that it can increase income.